The Role of Artificial Intelligence in Enhancing Digital Tourism Experiences - Aisha Ibrahim; Fatima Hassan; Zainab Usman (International Conference On Digital Advanced Tourism Management And Technology, 2023)
This study explores the integration of artificial intelligence (AI) in digital tourism to provide enhanced and personalized travel experiences. Through case studies of AI-powered chatbots, virtual assistants, and recommendation systems, the research demonstrates how AI transforms the tourism industry by improving customer engagement, operational efficiency, and decision-making. The paper concludes with insights into future trends and challenges in adopting AI for tourism development.